Faktor Determinan Waiting Time di IGD Hospital Nasional Guido Valadares - Noelio Auxilio Pedro Martins; Prima Dewi Kusumawati; Agusta Dian Ellina (Universitas Malahayati Lampung, 2026)
ABSTRACT Waiting time is an important indicator in assessing the quality of services in the Emergency Department (ED). Excessive waiting time may lead to delays in patient treatment, reduced patient satisfaction, and increased risk to patient safety. Several factors may influence waiting time in emergency services, including the availability of facilities and infrastructure, administrative processing time, and laboratory examination time. Hospital Nacional Guido Valadares, as a national referral hospital, also faces challenges in managing patient waiting times in the Emergency Department. This study aimed to analyze the influence of facilities and infrastructure, administrative processing time, and laboratory examination time on patient waiting time in the Emergency Department of Hospital Nacional Guido Valadares. This research employed a quantitative research design with a cross-sectional approach. The population consisted of patients receiving services in the Emergency Department, with a total sample of 115 respondents selected using purposive sampling. Data were collected using structured questionnaires and analyzed using logistic regression statistical analysis to determine the influence of each independent variable on patient waiting time. The results showed that most respondents perceived the availability of facilities and infrastructure and the administrative process as generally adequate, although several service constraints still contributed to delays in patient care. Logistic regression analysis indicated that facilities and infrastructure did not have a statistically significant effect on waiting time (p = 0.365). Similarly, administrative processing time did not show a statistically significant influence (p = 0.100; Exp(B) = 4.582), although patients experiencing slower administrative processes tended to have a higher probability of longer waiting times. In contrast, laboratory examination time showed a statistically significant effect on patient waiting time (p 0.05), indicating that it is the dominant factor influencing waiting time in the Emergency Department. In conclusion, improving the efficiency of laboratory examination services is a key strategy to reduce patient waiting time in the Emergency Department of Hospital Nacional Guido Valadares. Strengthening administrative service systems, optimizing laboratory workflow, and enhancing coordination among hospital units are essential to improve the quality of emergency healthcare services. Keywords: Waiting Time, Facilities and Infrastructure, Administrative Processing Time, Laboratory Turnaround Time, Emergency Department.ABSTRAK Waiting time atau waktu tunggu pasien merupakan salah satu indikator penting dalam menilai mutu pelayanan di Instalasi Gawat Darurat (IGD). Waktu tunggu yang terlalu lama dapat berdampak pada keterlambatan penanganan pasien, menurunkan kepuasan pasien, serta berpotensi meningkatkan risiko keselamatan pasien. Berbagai faktor dapat memengaruhi waiting time di IGD, di antaranya sarana dan prasarana pelayanan, waktu administrasi, serta waktu pemeriksaan laboratorium. Hospital Nacional Guido Valadares sebagai rumah sakit rujukan nasional juga menghadapi tantangan dalam pengelolaan waktu tunggu pasien di IGD. Penelitian ini bertujuan untuk menganalisis pengaruh sarana dan prasarana, waktu administrasi, serta waktu laboratorium terhadap waiting time pasien di IGD Hospital Nacional Guido Valadares. Penelitian ini menggunakan desain penelitian kuantitatif dengan pendekatan cross sectional. Populasi dalam penelitian ini adalah pasien yang mendapatkan pelayanan di IGD, dengan jumlah sampel sebanyak 115 responden yang dipilih menggunakan teknik purposive sampling. Pengumpulan data dilakukan menggunakan kuesioner terstruktur dan dianalisis menggunakan analisis statistik regresi logistik untuk mengetahui pengaruh masing-masing variabel terhadap waiting time pasien. Hasil penelitian menunjukkan bahwa sebagian besar responden menilai sarana dan prasarana serta proses administrasi berada pada kategori cukup baik, namun masih terdapat beberapa kendala yang menyebabkan keterlambatan pelayanan. Hasil analisis regresi logistik menunjukkan bahwa variabel sarana dan prasarana tidak berpengaruh signifikan terhadap waiting time (p = 0,365), sedangkan waktu administrasi juga tidak menunjukkan pengaruh yang signifikan secara statistik (p = 0,100; Exp(B) = 4,582). Sementara itu, waktu pemeriksaan laboratorium menunjukkan pengaruh yang signifikan terhadap waiting time pasien di IGD (p 0,05), sehingga menjadi faktor dominan yang memengaruhi lamanya waktu tunggu pasien. Berdasarkan hasil penelitian tersebut dapat disimpulkan bahwa percepatan proses pemeriksaan laboratorium menjadi faktor penting dalam upaya menurunkan waiting time pasien di IGD Hospital Nacional Guido Valadares. Oleh karena itu, diperlukan upaya peningkatan efisiensi pelayanan laboratorium, optimalisasi sistem pelayanan administrasi, serta penguatan koordinasi antar unit pelayanan untuk meningkatkan mutu pelayanan kegawatdaruratan di rumah sakit. Kata Kunci: Waiting Time, Sarana dan Prasarana, Waktu Administrasi, Waktu Laboratorium, Instalasi Gawat Darurat.